2019
DOI: 10.4103/jlp.jlp_106_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various risk factors associated with multidrug-resistant organisms isolated from diabetic foot ulcer patients

Abstract: AIMS: Diabetic foot ulcer is a dreaded complication of diabetes. Diabetic foot ulcer patients are often infected with multidrug resistant organism (MDRO) due to chronic course of the wound, inappropriate antibiotics treatment, frequent hospital admission, neuropathy, nephropathy, and peripheral vascular disease. MATERIALS AND METHODS: This prospective study was conducted in our 750 bedded hospital for a period of 6 months. The present study was undertaken to isolate various MDRO methicillin resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
6
14
1
Order By: Relevance
“…This came along with other studies conclusions where it was found that no single antibiotic used empirically offers adequate coverage for all potential bacteria found in diabetic foot ulcers [27]. In addition to that, poor penetration of antibiotics into the lower limb tissue due to peripheral arterial disease makes therapy less effective [28].…”
Section: Discussionsupporting
confidence: 58%
“…This came along with other studies conclusions where it was found that no single antibiotic used empirically offers adequate coverage for all potential bacteria found in diabetic foot ulcers [27]. In addition to that, poor penetration of antibiotics into the lower limb tissue due to peripheral arterial disease makes therapy less effective [28].…”
Section: Discussionsupporting
confidence: 58%
“…MDR organisms are predominantly isolated from wounds of diabetic foot patients compared to non-diabetic patients, which lead to the failure of empirical treatments and increased mortality and morbidity (28). A very high rate of antibiotic resistance was observed in this study, this result agrees with Datta et al (29) and Pal et al (30) results. The treatment of choice remains carbapenem or a combination of beta-lactam/ beta-lactamase inhibitors as mentioned elsewhere (31); however, in this study, resistance to these antibiotics was observed, with 22.2% of the microorganisms being resistant to imipenem and 16.6% being resistant to ertapenem (both are related to the carbapenem group); 55.5% were resistant to ampicillin/sulbactam, 44.4% to amoxicillin/clavulanic acid, and 16.6% to piperacillin/ tazobactam (the combination of beta-lactam/beta-lactamase inhibitor).…”
Section: Discussionsupporting
confidence: 89%
“…This occurs largely because of the inappropriate use of antibiotics and free access to antibiotics in many countries. Thus, treating physicians must identify the presence of MDR organisms and their associated risk factors, like hospitalization, irrational use of antibiotics, chronic wounds and duration of diabetes, to improve outcomes, as stated by Data et al [29] and Anvarinejad et al (29,33). Most patients had suffered from diabetes for a long time, and their foot ulcers remained unhealed for long time, e.g.…”
Section: Proteus Mirabilis Positive By Pcr For Beta-lactamases Genesmentioning
confidence: 99%
“…Other variables included in the model are well-known risk factors for the adverse outcomes of antibiotic treatment: prior antibiotic treatment, nasogastric tube, and low albumin level are all risk factors for Clostridoides difficile infection [ 19 , 20 ]. Peripheral vascular disease, central venous catheter, indwelling urinary catheter, and prior antibiotic treatment are risk factors for multidrug-resistance infection [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%